2022
DOI: 10.1152/advan.00118.2021
|View full text |Cite
|
Sign up to set email alerts
|

Interactive retrieval practice in renal physiology improves performance on customized National Board of Medical Examiners examination of medical students

Abstract: Retrieval practice improves long-term retention. Use of interactive retrieval practice in large group, in-person and online live classes, in combination with outside resources, is unreported for medical physiology classes. The primary study purpose was to compare student cohorts' performance with or without retrieval practice in renal physiology classes, relative to the national average on customized national examinations in renal physiology, non-physiology, and all questions. The secondary purpose was to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…An avenue that can assist in enhancing preparation for students can be through increased practice questions and simulated examination environments [ 28 ]. Classes that offer multiple opportunities for practice with interleaved lecture questions, post-lecture questions, and links to helpful reading resources not only improve examination performance but also student satisfaction [ 29 ]. Additionally, studies have found that increased practice problem completion, greater than at least 2000 in one study and 3500 in another, had significantly resulted in higher Step 1 scores [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…An avenue that can assist in enhancing preparation for students can be through increased practice questions and simulated examination environments [ 28 ]. Classes that offer multiple opportunities for practice with interleaved lecture questions, post-lecture questions, and links to helpful reading resources not only improve examination performance but also student satisfaction [ 29 ]. Additionally, studies have found that increased practice problem completion, greater than at least 2000 in one study and 3500 in another, had significantly resulted in higher Step 1 scores [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have addressed the importance of retrieval practice in preparing for exams [8,9,11,12,15,21] and the need for a support system for medical students, especially those who are struggling [1][2][3][4][5]. This study focused on a comparison of Step 1 performance and the students' usage of question banks and educational videos.…”
Section: Discussionmentioning
confidence: 99%
“…Active study methods, including retrieval practice, spaced repetition, and the use of practice questions and question banks (a pool of practice questions), have been shown to be effective means of improving students' learning and long-term retention [8][9][10][11]. Practice questions can specifically identify weak areas, improve students' metacognition and long-term retention, increase their knowledge, and improve their confidence when approaching standardized exams [12][13][14][15]. Specifically, recent research has focused on students' use of practice questions to prepare for board exams, including the USMLE Step 2 CK examination [16][17][18].…”
Section: Introductionmentioning
confidence: 99%